3D simulation of micro droplet impact on the structured superhydrophobic surface. (February 2022) - Hu, Anjie; Liu, Dong
Highlights: The micro droplet impact on a structured superhydrophobic surface is simulated with VOF model. Characteristics of both Cassie and Wenzel impact regimes are discussed. The Laplace pressure of the droplet promotes the impalement transition in the Cassie impact regime. The surface adhesion of the Wenzel impact regime decreases with the intrinsic contact angle. The height of the micro pillar also significantly influences the impact result. Abstract: In this work, the volume-of-fluid (VOF) model is applied to numerically study the micro droplet impact on the structured superhydrophobic surface with a large range of impact velocity. The droplet impact processes of both Cassie and Wenzel regimes are obtained and discussed. The influences of the intrinsic contact angle and pillar height on the impact are also studied in the simulation. The simulation results show that, due to the small diameter of the micro droplet, the effect of the Laplace pressure on the droplet impinging cannot be neglected, which could facilitate the impalement transition in the Cassie impact regime. The surface with a larger intrinsic contact angle can not only reduce the penetrate depth of the Cassie impact, but also significantly reduce the adhesion force of the surface in the Wenzel impact regime. When the intrinsic contact angle is large, the droplet can rebound even in the Wenzel impact regime. The height of the pillar also influences the bouncing ability of the droplet in the Wenzel regime. A shorter pillar is beneficial for droplet bouncing in the Wenzel impact regime while it is bad for maintaining the Cassie regime. These results can be used as a reference in understanding the mechanism of high-speed supercool droplet impact on anti-icing superhydrophobic surface and designing highly efficient anti-icing surfaces.